Balansa clover (Trifolium michelianum) - a forage legume for temperate pastures - Craig A.D.; Ballard R.A. (Legumes for Mediterranean forage crops, pastures and alternative uses, 2000)
Balansa clover is gaining increasing importance as a pasture legume across southern and eastern Australia. New cultivars are being developed which will broaden the species' adaptation and usage. Research is also being conducted on agronomic issues which impact on the species' performance in the field. This paper presents results from some of this work, details the key attributes of the species, describes the current commercial cultivars and future breeding objectives.
10. Meeting of the Mediterranean Sub-Network of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Pastures and Fodder Crops, 2000/04/04-09, Sassari (Italy)